LEF1 reduces tumor progression and induces myodifferentiation in a subset of rhabdomyosarcoma - Dräger, Julia; Simon-Keller, Katja; Sticht, Carsten; Marx, Alexander (OncoTarget, 2017)
Oncotarget | https://doi.org/10.18632/oncotarget.13887 Julia Dräger, Katja Simon-Keller, Tobias Pukrop, Florian Klemm, Jörg Wilting, Carsten Sticht, Kai Dittmann, Matthias Schulz, Ivo Leuschner, Alexander Marx,...